'Proton escalator' PEI and phosphotungstic acid containing nanofiber membrane with remarkable proton conductivity. Issue 12 (19th May 2021) - Sun, Xiuwei; Liu, Shumei; Wu, Qingyin; Zhang, Shan; Tian, Hongrui; Bai, Xue; Li, Zhuo; Lu, Ying; Liu, Shuxia
Abstract : Polyethyleneimine (PEI) and phosphotungstic acid (HPW) build an efficient proton transmission path. The segmental movement of flexible PEI speeds up the migration of protons, which acts as a 'proton-escalator'. Abstract : Polyethyleneimine (PEI) is expected to become a new type of proton conduction booster due to its high density amine and extremely high flexibility. Herein, a nanofiber membrane (eHPW-PEI) composed of PEI and phosphotungstic acid (H3 PW12 O40, HPW) was prepared by electrostatic spinning using polyvinylpyrrolidone (PVP) as an adhesive. In eHPW-PEI, the continuous H-bond network formed by HPW-PEI acid–base pairs, the segmental movement of highly flexible PEI and the well-tuned pathway of 1D nanofibers jointly prompt the fast transfer of protons under high temperature and low humidity conditions. The proton conductivity of eHPW-PEI with 25 wt% HPW (eHPW-PEI1 ) reached 1.6 × 10 −3 S cm −1 at 85 °C and 60% relative humidity (RH) and 3.7 × 10 −3 S cm −1 at 135 °C. This is the first time that the segmental movement of a highly flexible polymer is utilized to accelerate proton transfer, which may be considered as a 'proton-escalator'.